The road to Damascus passes through the Amazon. Chronicle of an announced conversion - Giménez Micó, José Antonio (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Mario Vargas Llosa’s novel El hablador (1987) is a parody of anthropological discourse and practice. This parody is carried out through the traditional rhetorical tactic of carrying to its limits, and thereby reducing to absurdity, what Vargas Llosa calls indigenous “conservationism” or “cultural environmentalism.” In order to discredit those who dare question the pure and simple assimilation of indigenous peoples to the dominant culture, Vargas Llosa uses as exemplum the presentation of a converso, a Saint and a visionary: that is, a character so “emotional”, so “irrationally” blinded by the deterritorialisation the Machiguengas are faced with that, instead of advocating their “conversion” to “modernity” or, at least, coming to the “reasonable” conclusion that this conversion is inevitable, he himself ends up “converting” –in the literal, mystical sense of the word– to their “primitive” world. This reduction to absurdity is such that the attitude and quixotic behaviour of the eponymous character seems so radical that even the reader who feels sympathy towards him will be virtually forced to recognise the illusory character of his determination.